Nonstandard FDTD Simulation-Based Design of CROW Wavelength Splitters. (2nd June 2011) - Okada, Naoki; Cole, James B.; Yamada, Shigeki; Ogawa, Kensuke; Katayama, Yoshifumi
Abstract : The finite-difference time-domain (FDTD) algorithm has been used in simulation-based designs of many optical devices, but it fails to reproduce high-Q whispering gallery modes (WGMs). On the other hand, the nonstandard (NS) FDTD algorithm can accurately compute WGMs and can be used to make simulation-based designs of WGM devices. Wavelength splitters using the coupled resonator optical waveguides (CROWs) based on WGM couplings have recently attracted attention because they are potentially ultracompact. In this paper, we design a CROW wavelength splitter using NS FDTD simulations and demonstrate high interchannel extinction ratios of over 20 dB.